2021
DOI: 10.15296/ijwhr.2022.10
|View full text |Cite
|
Sign up to set email alerts
|

Related Risk Factors for Pelvic Floor Disorders in Postpartum Women: A Cross-sectional Study

Abstract: Objectives: Pelvic floor disorders (PFDs) during pregnancy and after delivery, and related risk factors are still debatable topics for research. Thus, the aim of the present study was to assess the probable risk factors associated with PFDs in Iran. Materials and Methods: This cross-sectional study was conducted in two state and private hospitals in Tabriz, Iran from the 1st of June to the 31st of August, 2018. The participants were 650 postpartum women, aged between 15 and 47 years six months after delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…34 In the our study, more than 50% of the women were rural residents, and most of them do heavy labor work, such as woodworking, Carrying heavy objects from house to market and from market to house, which square measure nerve-wracking activities. 35 In our study, mothers who had 5 or more vaginal child birth were 4 times more likely to have PFD than those who did not have vaginal deliveries. This compares to a study done in the Gurage Zone which showed that repeated vaginal deliveries vaginal deliveries were associated with PFD linked to 4 or fewer vaginal deliveries.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…34 In the our study, more than 50% of the women were rural residents, and most of them do heavy labor work, such as woodworking, Carrying heavy objects from house to market and from market to house, which square measure nerve-wracking activities. 35 In our study, mothers who had 5 or more vaginal child birth were 4 times more likely to have PFD than those who did not have vaginal deliveries. This compares to a study done in the Gurage Zone which showed that repeated vaginal deliveries vaginal deliveries were associated with PFD linked to 4 or fewer vaginal deliveries.…”
Section: Discussionmentioning
confidence: 46%
“… 34 In the our study, more than 50% of the women were rural residents, and most of them do heavy labor work, such as woodworking, Carrying heavy objects from house to market and from market to house, which square measure nerve-wracking activities. 35 …”
Section: Discussionmentioning
confidence: 99%